Visitor Satisfaction Level at Sulili Hot Spring Natural Tourism in Pinrang Regency - Sahabuddin, Sahabuddin (Universitas Majalengka, 2024)
The study aims to determine the level of Visitor Satisfaction at the Sulili Hot Springs Natural Tourism, Pinrang Regency. This type of research is descriptive research. The population in this study were visitors to the Sulili Hot Springs, Pinrang Regency with a sample size of 40 visitors and sampling using accidental sampling. The sampling technique is based on drawing samples by chance. The study results indicate that the Level of Visitor Satisfaction at the Sulili Hot Springs Natural Tourism, Pinrang Regency is classified as high.